Stenting in Coarctation of the Aorta - Ahsan, Syed Ali; Hossain, Syed Sawkat; Patwary, Md Saifullah; Salim, Md Abu; Chowdhury, Rafique; Haque, KMHS Sirajul (University Heart Journal, 2011)
Narrowing of the aorta most commonly occurs in the region where the ductus arteriosus joins the aorta, i.e. at the isthmus just below the origin of the left subclavian artery. It is associated with other abnormalities, of which the most frequent are bicuspid aortic valve and ‘berry’ aneurysms of the cerebral circulation. Acquired coarctation of the aorta is rare but may follow trauma or occur as a complication of a progressive arteritis, Takayasu’s disease. A 21 years old young lady noted intermittent headache and occasionally weakness or cramps in the legs on walking from her early childhood. On examination her blood pressure in the upper limb 210 / 120 mm Hg, in lower limb was 100 / 60 mm Hg. There was radio-femoral delay and femoral pulse was weak. A systolic murmur is heard posteriorly. Radiological examination showed changes in the contour of the aorta and rib notching. ECG shows left ventricular hypertrophy. Echocardiography showed only concentric hypertrophy of LV. CT angiogram revealed coarctation of the aorta present with development of collaterals. Inspite of getting 3 different antihypertensive drugs her BP was uncontrolled. In our hospital her coarctation of the aorta was corrected by by endovascular stenting on the coarctation of the aorta. 5F, 7F & then 9F sheath, straight & J tiped terumo & J tip taflon coated 300 cm long wire was used. Predilatation was done by ballon used 3x10 mm over 0.34" J tip terumo wire @ 10 atm. Post dilatation was done by ballon used 7x20 mm @ 4 atm. Wall stent (Endoprosthesis) 9F was used. 1st Wall stent 14mm x 40mm self expanding and 2nd Wall stent 16mm x 60 mm, upper part covered the mouth of left subclavian artery. Result of stenting was good and procedure was uneventful. DOI: 10.3329/uhj.v6i2.7256 University Heart Journal Vol. 6, No. 2, July 2010 pp.103-106